Problems with capnography at high altitude. - Pattinson, K; Myers, S; Gardner-Thorpe, C (2004)
The aim of this study was to investigate why capnographs malfunction at high altitude, in order to suggest ways of improving instrument reliability. Four machines were decompressed to simulated high altitude and measurements taken. The study showed that the reduced air density at altitude has effects upon the pump, causing difficulty in entraining gas, and that high altitude has additional effects upon calibration of the instruments.